Influence of SBS polymers of various structure on the properties of semi-blown bitumen binders - Nebratenko, Dmitry Yuryevich; Boksha, Marianna Yuryevna; Isakov, Alexander Mikhailovich (Roads and Bridges - Drogi i Mosty, 2022)
The influence of styrene-butadiene-styrene block copolymers (SBS polymers) on the properties of binders based on bitumen has long been the subject of wide and comprehensive studies. This paper presents an analysis of the relationship between the molecular structure of SBS polymers and their effect on the physical and mechanical properties of paving binders based on bitumen from the oil refinery in the Salavat city, the Republic of Bashkiria (territory of Russia). The amount of SBS polymers in the binder did not exceed 5% (wt.). The data obtained showed a significant relationship between the functional parameters of the binders (penetration, elasticity, storage stability) and the content, the macromolecule spatial framework and the structure of the styrene-butadiene-styrene thermoplastic elastomers used. Wpływ kopolimerów blokowych styren-buta- dien-styren (SBS) na właściwości lepiszczy bitumicznych jest od dawna przedmiotem szerokich badań. W artykule przedstawiono analizę zależności między topologią polimerów SBS a ich wpływem na właściwości fizyczne i mechaniczne lepiszczy drogowych uzyskanych na bazie asfaltu z rafinerii w Saławacie, zlokalizowanej na terenie autonomicznej republiki Baszkirii, wchodzącej w skład Federacji Rosyjskiej. Zawartość polimeru SBS w lepiszczu nie przekroczyła w badaniu 5% (wagowo). Uzyskane wyniki potwierdziły istotny związek między parametrami funkcjonalnymi lepiszcza (penetracją, nawrotem sprężystym, stabilnością magazynowania) a zawartością polimeru w lepiszczu, strukturą zastosowanego elastomeru termoplastycznego SBS oraz konformacją (układem przestrzennym) jego makrocząsteczek.